2004
DOI: 10.1016/j.geomorph.2003.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Sonic anemometers in aeolian sediment transport research

Abstract: Fast response wind and turbulence instruments, including sonic anemometers are used more and more in the research of aeolian sediment transport. These instruments provide data on mean wind, but also on friction velocity, wind speed fluctuations and turbulence statistics, such as the U-W and W-T covariance (C UW and C WT ), which are a measure for the momentum flux and the sensible heat flux. This short paper will examine two problems that may arise when using sonic anemometers, namely the low/high frequency lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
131
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(133 citation statements)
references
References 36 publications
2
131
0
Order By: Relevance
“…The sound speed is averaged with three measurements along each axis, which depends on air density and is influenced by air temperature, therefore serving as an indicator of air temperature. Particularly, sonic anemometer-derived temperature is referred to as the sonic virtual temperature but not exactly the same as the virtual temperature, despite that the difference between them is substantially negligible (van Boxel et al, 2004). Given that the sound speed and sonic virtual temperature are related to each other (Kaimal and Businger, 1963), the sonic virtual temperature can be estimated as 2 (1 0.317 / ) (1 0.51 )…”
Section: Description Of Field Experiments and Analysis Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sound speed is averaged with three measurements along each axis, which depends on air density and is influenced by air temperature, therefore serving as an indicator of air temperature. Particularly, sonic anemometer-derived temperature is referred to as the sonic virtual temperature but not exactly the same as the virtual temperature, despite that the difference between them is substantially negligible (van Boxel et al, 2004). Given that the sound speed and sonic virtual temperature are related to each other (Kaimal and Businger, 1963), the sonic virtual temperature can be estimated as 2 (1 0.317 / ) (1 0.51 )…”
Section: Description Of Field Experiments and Analysis Methodsmentioning
confidence: 99%
“…For example, the WindMaster Pro of Gill Instruments explicitly identifies in the product manual that it bears rain rate up to 300 mm h −1 . Nevertheless, the sensors of the sonic anemometer are sensitive to impurities, such as the raindrop (van Boxel et al, 2004). In previous studies, data collected during precipitation are generally removed to adequately guarantee the quality controls.…”
Section: Introductionmentioning
confidence: 99%
“…Sweeps and ejections contribute to a 'bursting process' in the flow where low-speed ejections of fluid away from the bed are followed by high-speed sweeps of flow towards the bed, and this process has been found to be important in accounting for sediment transport in rivers (Best, 1993). However, field investigations by Sterk, Jacobs and van Boxel (1998), Schönfeldt and von Löwis (2003), van Boxel, Sterk and Arens (2004), Leenders, van Boxel and Sterk (2005) and Weaver (2008) have found that the majority of instances of high aeolian saltation flux are rather associated with sweeps and outward interactions, i.e. flow events that have instantaneous horizontal velocities greater than the mean (Figure 18 Best, 1993).…”
Section: 9mentioning
confidence: 99%
“…Such data can be measured at-a-point in the airflow by a sonic anemometer (see Box 18.1) and so the requirement for a log-linear velocity profile over a significant depth of boundary layer is dismissed. Measurements of the Reynolds shear stress are becoming more common in aeolian process research (van Boxel, Sterk and Arens, 2004;Weaver and Wiggs, 2010;Weaver, 2008), with fluctuating components measured at 10 Hz and shear stress averaged over 10 minutes showing a good correlation with sediment transport rates (Weaver, 2008).…”
Section: Measuring Shear Velocity (U * ) and Wind Stressmentioning
confidence: 99%
See 1 more Smart Citation